STATE POLICY OF UKRAINE IN THE FIELD OF ENVIRONMENTAL PROTECTION: CHALLENGES OF THE PRESENT TIMES - Trotsiuk, Nina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
environmental protection, which are based on the principles of a unified environmental policy of the Member States of the European Union. General scientific and special legal methods of scientific knowledge were applied in the course of scientific research, in particular: the system-structural method, the method of observation, the method of generalization, the methods of analysis, and synthesis. Results: the author figured that the state policy of Ukraine in the field of environmental protection is primarily aimed at the implementation and compliance with European environmental standards, which is an important factor in ensuring the implementation of the provisions of the Association Agreement. It was noted that over the past two years in Ukraine, the legal framework and mechanisms for introducing European standards into the environmental policy of Ukraine have been changed, and the work of state authorities and the entire community continues on the practical implementation of innovations to save the environment from ecocide. Discussion: the author analyzed the main directions of the state policy of Ukraine in the field of environmental protection, including the development, improvement, and implementation of environmental policy; appropriate legal regulation and implementation of state environmental control based on the “polluter pays” principle; implementation of ecosystem services; effective implementation of methods for assessing the damage caused by the aggressor country for further reparations; reforming the state system of monitoring the environment, information on the state of the environment (environmental information) and information support in the field of the environment.